New geographic records of Hamlets, Hypoplectrus spp. (Serranidae), in the Caribbean Sea - Williams, Ernest H., Jr.; Bunkley-Williams, Lucy; Rogers, Caroline S.; Fenner, Robert (Revista de Biología Tropical, 2006)
The exact number of species of hamlets, Hypoplectrus spp., in the Caribbean is controversial and the geographic distributions of these species/forms are poorly documented. We report Curaçao, Netherlands Antilles, as a new locality for the Barred Hamlet, H. puella (Cuvier), and Shy Hamlet, H. guttavarius (Poey); and St. John and St. Thomas, U.S. Virgin Islands, for the Tan Hamlet, Hypoplectrus sp. The Black Hamlet, H. nigricans (Poey), has previously been reported from Curaçao, but we did not see it there. Rev. Biol. Trop. 54 (Suppl. 3): 171-173. Epub 2007 Jan. 15